Theory and applications of satisfiability testing -- SAT 2020 : 23rd International Conference, Alghero, Italy, July 3-10, 2020, Proceedings /: 23rd International Conference, Alghero, Italy, July 3-10, 2020, Proceedings. (2020) - Unknown
No abstract available